Synthesis and performances for treating oily wastewater produced from polymer flooding of new demulsifiers based on polyoxyalkylated N, N‐dimethylethanolamine. (1st December 2014) - Zhang, Jian; Jing, Bo; Fang, Shenwen; Duan, Ming; Ma, Yongzhang
<x xml:space="preserve">Abstract</x> Usually, oily wastewater produced from polymer flooding (OWPF) was treated by cationic polymer in oilfield. In this paper, six block copolymers of ethylene oxide and propylene oxide were prepared by using N, N‐dimethylethanolamine (DMEA) as the acceptor (DMEA‐mnp and DMEA‐mnpq, n:m:p:q represented the weight ratio of different blocks). Most of DMEA products could perform well for treating OWPF, especially DMEA1231. Their performances were mainly affected by temperature. The reason of increasing oil removal performance of DMEA1231 with temperature was the decrease of interfacial dilational modulus (ε) with increasing temperature. When temperature raised up to 55°C, the ε of DMEA1231 had the minimum (1.5 l mN/m). Therefore, the OiW had the minimum (90 mg/l). Because DMEA1231 had the best performance, its flocculation kinetics was studied systemically. The results showed that the optimum condition for DMEA1231 was as follows: dosage was 300 mg/l, temperature was 55°C, stirring speed was 200 rpm and stirring time was 5 min. At last, the offshore oil field test was carried out to check the DMEA1231 performance. The result showed that at the optimum condition, DMEA1231 could perform as well as the cationic polymer. The most important thing was that flocs of DMEA1231 were not viscous and floated on the surface of the water. The results obtained by this paper provide a good choice for the treatment of OWPF in offshore oilfield to avoid the formation of viscous flocs. Copyright © 2014 John Wiley & Sons, Ltd.